Effects of amino acid substitutions in the VP2 B-C loop on antigenicity and pathogenicity of serotype Asia1 foot-and-mouth disease virus - Xue Mei; Wang Haiwei; Li Wan; Zhou Guohui; Tu Yabin; Yu Li (Virology Journal, 2012)
Abstract Background Foot-and-mouth disease virus (FMDV) exhibits a high degree of antigenic variability. Studies of the antigenic diversity and determination of amino acid changes involved in this diversity are important to the design of broadly protective new vaccines. Although extensive studies have been carried out to explore the molecular basis of the antigenic variation of serotype O and serotype A FMDV, there are few reports on Asia1 serotype FMDV. Methods Two serotype Asia1 viruses, Asia1/YS/CHA/05 and Asia1/1/YZ/CHA/06, which show differential reactivity to the neutralizing monoclonal antibody (nMAb) 1B4, were subjected to sequence comparison. Then a reverse genetics system was used to generate mutant versions of Asia1/YS/CHA/05 followed by comparative analysis of the antigenicity, growth property and pathogenicity in the suckling mice. Results Three amino acid differences were observed when the structural protein coding sequences of Asia1/1/YZ/CHA/06 were compared to that of Asia1/YS/CHA/05. Site-directed mutagenesis and Immunofluorescence analysis showed that the amino acid substitution in the B-C loop of the VP2 protein at position 72 is responsible for the antigenic difference between the two Asia1 FMDV strains. Furthermore, alignment of the amino acid sequences of VP2 proteins from serotype Asia1 FMDV strains deposited in GenBank revealed that most of the serotype Asia1 FMDV strains contain an Asn residue at position 72 of VP2. Therefore, we constructed a mutant virus carrying an Asp-to-Asn substitution at position 72 and named it rD72N. Our analysis shows that the Asp-to-Asn substitution inhibited the ability of the rD72N virus to react with the MAb 1B4 in immunofluorescence and neutralization assays. In addition, this substitution decreased the growth rate of the virus in BHK-21 cells and decreased the virulence of the virus in suckling mice compared with the Asia1/YS/CHA/05 parental strain. Conclusions These results suggest that variations in domains other than the hyper variable VP1 G-H loop (amino acid 140 to 160) are relevant to the antigenic diversity of FMDV. In addition, amino acid substitutions in the VP2 influenced replicative ability and virulence of the virus. Thus, special consideration should be given to the VP2 protein in research on structure-function relationships and in the development of an FMDV vaccine.